FACULTY OF MUSIC IN EDUCATIONAL SPACE OF A TOWN - Olga V. Tulinova (Moscow Polytechnic University, 2016)
The article traces the history and development of the Faculty of Music Education of I.A. Bunin Elets State University, dwells upon the main areas of its activity, shows its role for Elets' social and cultural life.